2021
DOI: 10.1021/acs.jpclett.1c03226
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous NH3-Induced Resistance Enhancement in Halide Perovskite MAPbI3 Film and Gas Sensing Performance

Abstract: Despite the growing interest in halide perovskite-based NH3 sensors, the NH3 sensing mechanism is still not well understood. Here, we report an anomalous behavior of resistance enhancement in CH3NH3PbI3(MAPbI3) perovskite films upon exposure to NH3 gas, which is contrary to a resistance drop trend in previously reported perovskites. We propose a NH3 sensing mechanism in which the anomalous resistance enhancement is dominated by grain boundaries of perovskites. It is demonstrated that NH3 molecules can substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Phase changes of perovskites result in significant differences in their electrical properties, resulting in a response of 472% at 30 ppm of NH 3 . 77 The NH 3 gas detection mechanism remains unclear; however, numerous studies have proposed perovskite-based NH 3 sensors. Casanova-Chafer et al fabricated a sensor with graphene and MAPbI 3 .…”
Section: Chemiresistive Gas Sensorsmentioning
confidence: 99%
“…Phase changes of perovskites result in significant differences in their electrical properties, resulting in a response of 472% at 30 ppm of NH 3 . 77 The NH 3 gas detection mechanism remains unclear; however, numerous studies have proposed perovskite-based NH 3 sensors. Casanova-Chafer et al fabricated a sensor with graphene and MAPbI 3 .…”
Section: Chemiresistive Gas Sensorsmentioning
confidence: 99%
“…202 Li et al showed an anomalous behavior of resistance enhancement dominated by the grain boundaries in MAPbI 3 perovskite films upon exposure to NH 3 gas. 203 This occurs mainly due to the substitution of MA + cations by NH 3 molecules and the formation of insulating NH 4 PbI 3 ÁMA intermediate layers on the surface of the crystal grains. The sensor showed a gas response of 472% toward 30 ppm of NH 3 at room temperature.…”
Section: Limit Of Detection (Lod)mentioning
confidence: 99%
“…158 The performance of gas sensors based on different metal halide perovskites is summarized in Table 1. 14,33,36,37,142,143,149,151,158–208…”
Section: Gas Sensing Applications Of Perovskites and Their Heterostru...mentioning
confidence: 99%
“…[18][19][20] However, the effect of gases that are present in a limited concentration in the atmosphere and many controlled conditions, can be detrimental owing to their strong interaction with MAPbI 3 . 21,22 Limited research has been conducted in this area which can provide critical insights into increasing the stability and performance of the perovskitebased devices. 23,24 In this work, we show through the use of a variety of gases that carbon monoxide (CO) has strong interaction with MAPbI 3 .…”
Section: Introductionmentioning
confidence: 99%